The Endeavor of Translating the Quran - Meza, Gabriela Aurora Mondragon (Fakultas Dakwah UIN KHAS Jember, 2025)
Translating a text such as the Holy Qur'an is complex. The aim of this research is to: 1) explain the characteristics of various Qur'anic translations based on scholarly analysis into Spanish, 2) discuss the task of translating the Qur'an using basic communication model elements, 3) reflect on the impact of translation on non-Arabic-speaking communities like Mexico and Colombia, and 4) promote AI use as a tool, not authority. This research uses qualitative analysis to explore Qur'anic translation into Spanish, focusing on translator types, challenges, and cultural influences. The results of this research are: 1) An analysis of Spanish Qur'anic translations, addressing challenges like linguistic depth and cultural context, categorized based on Gottlieb's theory. 2) A communication model framework for translation, highlighting the translator's role in bridging cultural gaps. 3) Insights from interviews with Muslim converts in Mexico and Colombia, showing the importance of translations for spiritual growth and the eventual study of the Qur'an in Arabic. 4) A proposal for using AI as a tool for translation, emphasizing the need for human oversight due to AI's lack of cultural sensitivity.